Analysis of the Impact of Local Government Expenditure on Happiness Index in Provinces in Indonesia - Pranoto, Alexander Nur Huda; Sihaloho, Estro Dariatno (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — The happiness index is an important indicator to examine the progress of a country’s development. This research is the first to study the impact of local government expenditure on happiness, particularly in Indonesia. Research Objectives — This study aims to investigate the impact of local government expenditure on happiness. Additionally, it examines the effect of GRDP per capita, school life expectancy, and inequality on happiness. Research Methods — This study used panel data from Statistics Indonesia and the Ministry of Finance in 2014, 2017, and 2021 for case studies in 34 provinces in Indonesia. The methods used were pooled least square, fixed effect model, random effect model, and quantile regression. Empirical Results — The estimation results showed that local government expenditure, GRDP per capita, school life expectancy, and inequality significantly affected the happiness index. The correlation between local government expenditure and inequality on the happiness index was negative in all quantiles. Meanwhile, the relationship between GRDP per capita and school life expectancy on the happiness index was positive in all quantiles. Implications — The negative impact of local government expenditure on happiness shows that local government expenditure is not optimal for development. Sub-optimal expenditure allocations, such as capital expenditure for infrastructure development, are lower than personnel expenditure, which makes people less happy. Therefore, the government needs to evaluate and improve the effectiveness of local government expenditure and allocate government expenditure that directly affects society, such as infrastructure development, education and health facilities, MSME financing, and the creation of new jobs.